Montgomery's Federal Taxes–35 Edition (Book). - Wittman, C. Wm. (The Accounting Review, 1955)
Reviews the book "Montgomery's Federal Taxes," 35th ed., by Philip Bardes Mark E. Richardson and James J. Mahon and John McCullough.